An Architectural Approach to Support the Development of Digital Educational Games in Computing - Genesio, Nikolas Oliver Sales; Silva, Williamson; Oliveira, Alessandreia Marta de; Valle, Pedro Henrique Dias (Anais do Workshop sobre Educação em Computação (WEI); 2025: Anais do XXXIII Workshop sobre Educação em Computação, 2025)
The increasing use of Digital Educational Games (DEGs) to support computing education has been observed over the years to improve student engagement and motivation. However, many of these DEGs face challenges in capturing students’ interest, resulting in demotivation and disinterest. In this context, this study presents the Reference Architecture (RA), denominated RADEG, to support the development of DEGs aimed at teaching Computing. The evaluation results indicated that the specialists accepted the RA well, considering different requirements, such as learnability, playability, and maintainability. However, security and entertainment requirements need to be addressed in the evolution of RA.